Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.polymer.2016.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of bisphenol A on the polymerisation and network properties of an aromatic benzoxazine

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms ABSTRACT: A series of reactive blends, comprising a commercial benzoxazine monomer, 2,2- bis(3,4-dihydro-3-phenyl-2H-1,3-benzoxazine)propane, and bisphenol A is prepared andcharacterized. Thermal analysis and dynamic rheology reveal how the introduction of up to 15 wt % bisphenol A le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
0
13
1
Order By: Relevance
“…A 6.9–9.5% weight loss was observed at this temperature range, which can be attributed to the degradation of phenolic terminal groups at the chain end in the networked polybenzoxazines (Scheme ) . Ishida et al also reported such degradation (first mass loss at 150–200 °C) in cured bisphenol‐A benzoxazine (B‐a)/bisphenol‐A (BPA) blends, where BPA branches or side chains were formed with higher bisphenol‐A content . The major amount of weight loss in NPBzs was observed only above 250 °C (17–32%), thus implies that the main chain degradation in NPBzs occurring quite similar to poly(T‐Bz) (26%) or other traditional polybenzoxazines at higher temperature …”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…A 6.9–9.5% weight loss was observed at this temperature range, which can be attributed to the degradation of phenolic terminal groups at the chain end in the networked polybenzoxazines (Scheme ) . Ishida et al also reported such degradation (first mass loss at 150–200 °C) in cured bisphenol‐A benzoxazine (B‐a)/bisphenol‐A (BPA) blends, where BPA branches or side chains were formed with higher bisphenol‐A content . The major amount of weight loss in NPBzs was observed only above 250 °C (17–32%), thus implies that the main chain degradation in NPBzs occurring quite similar to poly(T‐Bz) (26%) or other traditional polybenzoxazines at higher temperature …”
Section: Resultsmentioning
confidence: 88%
“…However, all NPBzs showed a very high thermal stability (50–150 °C higher) as compared to previously reported LPBz based on bifunctional benzoxazine and MR (i.e., 3a, Table ) . Thermal stability was also found to be higher in relative to commercial bisphenol‐A based polybenzoxazine (MT35600: T d5 = 289 °C; T d20 = 355 °C) . The char residue was varied from 65 to 79% and in the order of poly(T‐Bz) ≥ DHN > PG > MR > HQ > 3a (55%) > poly(B‐a) (36%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polybenzoxazines feature for special characteristics such as a moderate-to-high thermal property, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] moderate electrical property, [19] low water absorption, [20] and low surface energy. [21] Low-dielectric benzoxazines have been reported (1) by Chang et al through Mannich condensation of bisphenol F/ 4-(trifluoromethyl)aniline/formaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…However, phenols can not only catalyze the ring-opening reaction of benzoxazine monomers and lower their curing temperature, but will also react with benzoxazines through electrophilic substitution reactions to form similar chemical structures to polybenzoxazine. Hamerton et al 49 added 15 wt% of bisphenol-A into bisphenol-A/aniline benzoxazine (BA-a), and found that the exothermic peak temperature of BA-a was decreased from 245 C to 215 C because of the catalytic action of phenol. Kolanadiyil et al 50 studied the catalytic effect of various phenolic nucleophiles on a trifunctional benzoxazine (T-BZ).…”
Section: Introductionmentioning
confidence: 99%